La mirada del Quetzal desplazada por el ojo del águila imperial. Intervenciones en Centroamérica - Castañeda Hernández, Jaime A (2014)
The reconstruction of the past in the present in pursuit of identity construction, does not necessarily address the category of truth or falsity.  It is enough to say the memory is not an adequate expression when used in singular but to talk about memories, in  plural, to study aspects of  Central American geographical dimension and  cultural dimension represented by the image of the  bird that characterizes the region –the quetzal--, in contrast to the interventionism  deployed by the United States, represented by its emblematic bold eagle